If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(x + -8) = 7 + 8x Reorder the terms: 9(-8 + x) = 7 + 8x (-8 * 9 + x * 9) = 7 + 8x (-72 + 9x) = 7 + 8x Solving -72 + 9x = 7 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -72 + 9x + -8x = 7 + 8x + -8x Combine like terms: 9x + -8x = 1x -72 + 1x = 7 + 8x + -8x Combine like terms: 8x + -8x = 0 -72 + 1x = 7 + 0 -72 + 1x = 7 Add '72' to each side of the equation. -72 + 72 + 1x = 7 + 72 Combine like terms: -72 + 72 = 0 0 + 1x = 7 + 72 1x = 7 + 72 Combine like terms: 7 + 72 = 79 1x = 79 Divide each side by '1'. x = 79 Simplifying x = 79
| S-2=25 | | 7x-8+2x=2+9x-9 | | 6x-13-3x=5x-6 | | 3.25n=54 | | Ln(9x+11)-Lynx= | | 12x+8=80 | | 12(x+9)=108 | | x^3-343=-0 | | -2(d-3d)=12 | | 6x+66=144 | | 2.2k=6.16 | | 6-(3y-2)=1-4y | | z^2+24z+c=0 | | 3x+y-2z=22 | | 10.6n+15=205.8 | | 6-8x+5x-2= | | s^2+17s+c=0 | | 19-(x+5)=6x-7 | | X+3.3=9.9 | | 3x+21=5y | | 12y+2=8 | | 5-4[5-(x-3)]= | | -7(x+6)=-6x-6 | | (6+3)+(2x-4x)=5 | | 2x-5x-14=0 | | 550(.15)=x | | S-8=5 | | (6+3)+(2x+4x)=5 | | 9.95n+3.59=33.44 | | 7(4x+5)=119 | | 9.95n+3.59=33.4 | | (3x+5y)(5x-6y)= |